2020
DOI: 10.3390/pr9010062
|View full text |Cite
|
Sign up to set email alerts
|

Modified Multi-Crossover Operator NSGA-III for Solving Low Carbon Flexible Job Shop Scheduling Problem

Abstract: Low carbon manufacturing has received increasingly more attention in the context of global warming. The flexible job shop scheduling problem (FJSP) widely exists in various manufacturing processes. Researchers have always emphasized manufacturing efficiency and economic benefits while ignoring environmental impacts. In this paper, considering carbon emissions, a multi-objective flexible job shop scheduling problem (MO-FJSP) mathematical model with minimum completion time, carbon emission, and machine load is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the early stage, the constructive approach, widely known as NEH [10], is probably the one mostly refined and modified by other authors [11]. On the other hand, many meta-heuristics and their modified approaches have been applied to solve FSSP, such as particle swarm optimization [12,13], simulated annealing [14], genetic algorithm [13,15,16], ant colony optimization [7], and firefly algorithm [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage, the constructive approach, widely known as NEH [10], is probably the one mostly refined and modified by other authors [11]. On the other hand, many meta-heuristics and their modified approaches have been applied to solve FSSP, such as particle swarm optimization [12,13], simulated annealing [14], genetic algorithm [13,15,16], ant colony optimization [7], and firefly algorithm [17].…”
Section: Introductionmentioning
confidence: 99%
“…These systems can be as simple as spreadsheets with basic functionalities (e.g., Excel) or more complex, allowing advanced users with more experience to obtain graphical representations, visualize performance metrics and have access to effective optimization methods. Some modern example of successful approaches are presented in [7][8][9][10].…”
Section: Scheduling Problemsmentioning
confidence: 99%
“…Of these two approaches, the one that stands out is the one that uses approximation algorithms, given its efficiency and possibility of being used in production environments of real industries. Some examples of successful approaches are presented in [9,20,21].…”
Section: Job Shop Problemmentioning
confidence: 99%
“…Considering carbon emissions, Sun et al [14] establish a multiobjective flexible job shop scheduling problem (MO-FJSP) mathematical model with minimum completion time, carbon emission, and machine load. To solve this problem, they study six variants of the non-dominated sorting genetic algorithm-III (NSGA-III) and from the experimental results, it can be concluded that the NSGAIII-COE has significant advantages in solving the low carbon MO-FJSP.…”
Section: Scheduling and Planning Issuesmentioning
confidence: 99%